Coffee silverskin: Characterization of B-vitamins, macronutrients, minerals and phytosterols. (15th March 2022) - Nzekoue, Franks Kamgang; Borsetta, Germana; Navarini, Luciano; Abouelenein, Doaa; Xiao, Jianbo; Sagratini, Gianni; Vittori, Sauro; Caprioli, Giovanni; Angeloni, Simone
Highlights: Nutritional composition of coffee silverskin (CSS) from arabica coffee. Comprehensive assessment of macrominerals (7) and microminerals (23) in CSS. Vitamin B3 (2.51–3.07 µg/g) and vitamin B2 (0.18–0.20 µg/g) are present in CSS. Phytosterols analysis revealed high levels of β-sitosterol (77.1 ± 2.8 mg/kg). Abstract: The present study assessed the nutritional composition of coffee silverskin (CSS) obtained from arabica roasted coffee. Following validated analytical methods, CSS resulted to be a high source of proteins (14.2 g/100 g) and dietary fibers (51.5 g/100 g). Moreover, the mineral analysis revealed high contents of calcium (1.1 g/100 g) and potassium (1.0 g/100 g). To date, this study provided the widest mineral profile of CSS with 30 minerals targeted including 23 microminerals with high levels of iron (238.0 mg/kg), manganese (46.7 mg/kg), copper (37.9 mg/kg), and zinc (31.9 mg/kg). Moreover, vitamins B2 (0.18–0.2 mg/kg) and B3 (2.5–3.1 mg/kg) were studied and reported for the first time in CSS. β-sitosterol (77.1 mg/kg), campesterol, stigmasterol, and Δ5-avenasterol, were also observed from the phytosterol analysis of CSS with a total level of 98.4 mg/kg. This rich nutritional profile highlights the potential values of CSS for innovative reuses in bioactive ingredients development.